Revision of Colochela (Hymenoptera, Tenthredinidae) - Niu, Gengyun; Wei, Meicai (Zootaxa, 2016)
Colochela Malaise, 1937 is removed from synonymy with Neocolochelyna Malaise, 1937, and re-established. The genus and its type species C. rufidorsata Malaise, 1937 are redescribed based on types and new material. C. nigrata Wei & Niu, sp. nov. and C. zhongi Wei & Niu, sp. nov. are described. A key separating Colochelyna Konow, 1898, Colochela and Neocolochelyna, and a key to species of Colochela are provided. Colochela and C. rufidorsata are new records for Nepal and Thailand. The distribution of Colochela is briefly discussed.